Household pottery of an urban noble house and craftsmen in Visegrád - Bence Góra (Dissertationes Archaeologicae: Ex Instituto Archaeologico Universitatis de Rolando Eötvös Nominatae, 2024)
In 2003–2004, the King Matthias Museum in Visegrád conducted archaeological excavations at 5 Rév Street, Visegrád. The fieldwork brought to light, besides an already known late medieval house and a glass workshop of outstanding importance, some more buildings and the excellently preserved part of a street pavement. The study presents the pottery finds obtained by the excavations.